Assessing the benefits of five years of different approaches to treatment of urogenital schistosomiasis: A SCORE project in Northern Mozambique. - Phillips,AE; Gazzinelli-Guimaraes,PH; Aurelio,HO; Ferro,J; Nala,R; Clements,M; King,CH; Fenwick,A; Fleming,FM; Dhanani,N (PLoS Neglected Tropical Diseases, 2017)
BACKGROUND: In Mozambique, schistosomiasis is highly endemic across the whole country. The Schistosomiasis Consortium for Operational Research and Evaluation (SCORE) coordinates a five-year study that has been implemented in various African countries, including Mozambique. The overall goal of SCORE was to better understand how to best apply preventive chemotherapy with praziquantel (PZQ) for schistosomiasis control by evaluating the impact of alternative treatment approaches. METHODS: This was a cluster-randomised trial that compared the impact of different treatment strategies in study areas with prevalence among school children of ≥21% S. haematobium infection by urine dipstick. Each village was randomly allocated to one of six possible combinations of community-wide treatment (CWT), school-based treatment (SBT), and/or drug holidays over a period of four years, followed by final data collection in the fifth year. The most intense intervention arm involved four years of CWT, while the least intensive arm involved two years of SBT followed by two consecutive years of PZQ holiday. Each study arm included 25 villages randomly assigned to one of the six treatment arms. The primary outcome of interest was change in prevalence and intensity of S. haematobium among 100 children aged 9-to-12-years that were sampled each year in every village. In addition to children aged 9-to-12 years, 100 children aged 5-8 years in their first-year of school and 50 adults (aged 20-55 years) were tested in the first and final fifth year of the study. Prevalence and intensity of S. haematobium infection was evaluated by two filtrations, each of 10mL, from a single urine specimen. PRINCIPAL FINDINGS: In total, data was collected from 81,167 individuals across 149 villages in ten districts of Cabo Delgado province, Northern Mozambique. Overall PZQ treatment resulted in a significant reduction in the prevalence of S. haematobium infection from Year 1 to Year 5, where the average prevalence